The identification and validation of Auger electron-emitting radiopharmaceuticals targeting telomerase for cancer therapy - Jackson, M (2013)
Telomerase is expressed in the majority (>85%) of tumours but not in differentiated normal tissue. This enzyme catalyses the elongation of telomeres – a process critical for continued cell proliferation. Telomerase is a potential novel target for molecularly-targeted radiotherapy (mRT), due to its nuclear localization and expression profile. The radiolabelling of telomerase inhibitors may accelerate and enhance the cytotoxicity of such molecules, as a result of irradiation of the DNA. An oligonucleotide targeting telomerase RNA (hTR), shown to inhibit enzyme activity in vitro, was selected for study. Complementary and non-targeting control oligonucleotides were conjugated to a metal chelator (DTPA) to allow radiolabelling with indium-111. The radioiodination of MST-312, BIBR-1532 and flavonoid-derived small molecule inhibitors of telomerase was also pursued. The inhibitory activity of the candidate molecules was analysed using the telomeric repeat amplification protocol (TRAP). The internalization of inhibitors was assessed by gamma-counting following cell lysis. The clonogenic assay was employed to measure the effect of modified inhibitors on cell survival. Small molecule telomerase inhibitors were modified for labelling with iodine-123, which led to a modest decrease in inhibitory potency, compared to the parent molecules. Radiolabelled small molecules exhibited poor stability and internalization into cancer cells, so were unsuitable for mRT. Modified oligonucleotides potently inhibited telomerase activity, whereas a non-targeting oligonucleotide exhibited no inhibitory activity. Indium-111 radiolabelled oligonucleotides decreased the clonogenic survival of telomerase-positive breast cancer cells but not telomerase-negative cells, in a sequence-specific manner. Accordingly, complementary radiolabelled oligonucleotides were found to induce the DNA damage marker γH2AX. Oligonucleotides localized to nuclear Cajal bodies, the sites of telomerase assembly, in a proportion of cancer cells. Telomerase inhibitors of different classes were radiolabelled with Auger electron-emitting radionuclides, and delivered to cells. Radiolabelled oligonucleotides targeting telomerase significantly reduced the clonogenicity of cancer cells in vitro. This study represents a novel approach for the mRT of telomerase-positive cancers.